Kriminaliteta v Sloveniji v letu 2009 - Lukan, Andrej (Revija za kriminalistiko in kriminologijo, 2010)
The article presents data on crime dealt with by the Slovene police. In 2009, the police forwarded criminal complaints and reports supplementing criminal complaints to state prosecutors in relation to 87,465 criminal offence, which is 6.8% more than in 2008. The share of solved crimes rose from 45.1% to 48.3%. The increase of criminal offences and their clearance rate have been most affected by a rise in criminal offences against marriage, family and youth. In the framework of general crime, a slight increase was noted in the proportion of sexual offences, while the number of crimes against life and limb, and against property remained at the same level as the year before. The same applies to juvenile delinquency. The extent of economic crime has grown, as has the proportion of offences by organised crime. A substantial rise in crimes of corruption and the abuse of illicit drugs was also noted in 2009, while the number of computer related criminal offences and offences of prohibited crossing of the state border or territory decreased significantly. A ten-year comparison indicates a rise in the number of criminal offfences until 2006, then the number began to level off but again began to rise in 2009. The number of criminal offences against life and limb has not changed much. The number of more serious criminal offences, such as murder, manslaughter, particularly serious aggravated assaults and aggravated assaults has been slightly falling in this period, but not continually, while the proportion of sexual offences has oscillated. Criminal offences against marriage, family and youth had already begun to increase before the legislative amendments on 2008. Among criminal offences against property, which represent approximately two thirds of crime, an increase of less serious forms of thefts and some other minor property offences was noted, while the number of more serious criminal offences against property has not significantly changed. The extent of juvenile crime diminished in 2009 more than twofold in comparison to the period ten years ago. The number of criminal offences of economic and organised crime was subject to greater or lesser oscillation during this period.
Keywords: kazniva dejanja; kriminaliteta; policija; Slovenija; statistični podatki